Creating an Infrastructure for Comparative Effectiveness Research in Emergency Medical Services. (May 2014) - Seymour, Christopher W.; Kahn, Jeremy M.; Martin‐Gill, Christian; Callaway, Clifton W.; Angus, Derek C.; Yealy, Donald M.; Shah, Manish N.
Abstract Objectives Emergency medical services (EMS) providers deliver the initial care for millions of people in the United States each year. The Institute of Medicine noted a deficit in research necessary to improve prehospital care, created by the existence of data silos, absence of long‐term outcomes, and limited stakeholder engagement in research. This article describes a regional effort to create a high‐performing infrastructure in southwestern Pennsylvania addressing these fundamental barriers. Methods Regional EMS records from 33 agencies in January 2011 were linked to hospital‐based electronic health records (EHRs) in a single nine‐hospital system, with manual review of matches for accuracy. The use of community stakeholder engagement was included to guide scientific inquiry, as well as 2‐year follow up for patient‐centered outcomes. Results Local EMS medicine stakeholders emphasized the limits of single‐agency EMS research and suggested that studies focus on improving cross‐cutting, long‐term outcomes. Guided by this input, more than 95% of EMS records (2, 675 of 2, 800) were linked to hospital‐based EHRs. More than 80% of records were linked to 2‐year mortality, with more deaths among EMS patients with prehospital hypotension (30.5%) or respiratory distress (19.5%) than chest pain (5.4%) or nonspecific complaints (9.4%). Conclusions A prehospital comparative effectiveness research infrastructure composed of patient‐level EMS data, EHRs at multiple hospitals, long‐term outcomes, and community stakeholder perspectives is feasible and may be scalable to larger regions and networks. The lessons learned and barriers identified offer a roadmap to answering community and policy‐relevant research questions in prehospital care.